The role of family mediation in dealing with trust crises resulting from digital infidelity: An Islamic family law perspective - Mamlu'atur Rohmah; Musleh Harry (Asy-Syari’ah : Jurnal Hukum Islam, 2026)
The importance of this study is based on the rapid digitization that has triggered the phenomenon of digital infidelity, which has caused a crisis of trust in households. The purpose of this study is to analyze the impact of digital infidelity on household stability, examine the views of Islamic family law on this phenomenon, and explore the effectiveness of family mediation as a solution to conflict resolution. The research method used is normative legal research using an interpretive library research method. The results of this study comprehensively describe three main points: first, digital infidelity is identified as a form of emotional betrayal that causes deep psychological impacts, anxiety, and damage to the privacy of the domestic sphere. Second, in the view of Islamic family law, this behavior is classified as a violation of the principles of amanah and tsiqah and falls under the category of zina qalbi (adultery of the heart), which damages the sacred essence of the marriage contract. Third, the role of family mediation through the principles of tahkim and islah has proven to be very strategic as an instrument of moral and spiritual reconciliation that can restore trust between spouses through an approach based on justice ('adl), deliberation (syura), and compassion (rahmah). This study concludes that strengthening an adaptive mediation model for digital ethics is crucial in maintaining moral resilience and preventing the disintegration of Muslim families in the modern era.